BNBM : synergic innovation targeting the commanding heights - Li, Jizhen; Liu, Lijuan (London : Tsinghua University School of Economics and Management, 2017)
The case focuses on BNBM, the only national-level innovative enterprise in the new building materials industry in China, which has been focusing on independent innovation and technological breakthroughs in the gypsum board sector for many years. The case describes how BNBM, a state owned enterprise, promoted innovation and development and completed a technological development plan.
Originally Published InLi, J., & Liu, L. (2017). BNBM: Synergic Innovation Targeting the Commanding Heights. 1-817-311. Beijing, China: Tsinghua SEM Chinese Business Case Center.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Bei xin jian cai (ji tuan) you xian gong si (China) -- Case studies; Technological innovations -- China -- Case studies; Drywall -- China